Forkhead box O (FOXO) 3 modulates hypoxia-induced autophagy through AMPK signalling pathway in cardiomyocytes. Issue 3 (17th June 2016) - Chi, Yunpeng; Shi, Conghong; Zhao, Yang; Guo, Chengjun
Abstract : Autophagy is promoted as a response to such environmental stress conditions as ATP depletion and excessive accumulation of reactive oxygen species (ROS). Multiple signalling pathways, including AMP-activated protein kinase (AMPK), are indicated to promote autophagy in ischaemic/hypoxic (I/R) heart. However, it's far more to clarify the orchestrated cross-talk between AMPK and other signalling pathways in the autophagy. In the present study, we investigated the autophagy induction by hypoxia in Rat H9C2 cardiomyocytes with LC3-EGFP reporter, EM and Western blot analysis. Then, we examined the promotion of forkhead box O (FOXO) 3, one member of FOXO transcriptional protein family, by hypoxia in Rat H9C2 cells and determined the mediation of FOXO 3 in the hypoxia-induced autophagy in H9C2 cells. In addition, we investigated the role of AMPK signalling in the FOXO3-mediated, hypoxia-induced autophagy in H9C2 cells. It was demonstrated that hypoxia induced significant autophagy in H9C2 cells, via promoting autophagic vesicles, inducing the conversion of LC3-I to LC3-II and up-regulating autophagy-related (ATG) markers. Moreover, FOXO3 was up-regulated by the hypoxia in H9C2 cells; and the knockdown of FOXO3 significantly reduced the hypoxia-induced autophagy. In addition, AMPK signalling was significantly promoted by hypoxia in H9C2 cells, and the chemical manipulation of AMPK exerted significant influence on the hypoxia-induced autophagy and on the FOXO3 level. In conclusion, FOXO3 regulated the hypoxia-induced autophagy in cardiomyocytes, and AMPK mediated the FOXO3 promotion during the autophagy induction by hypoxia, implying the key regulatory role of FOXO3 and AMPK signalling in the hypoxia-induced autophagy in cardiomyocytes.